Laboratory protocols in fungal biology : current methods in fungal biology - Ayyachamy, Manimaran; Gupta, Vijai Kumar; O'Donovan, Anthonia; Tuohy, Maria G.; Turner, Kevin M. (Fungal biology, 2013)
Fungi and their biomolecules are today being explored in a variety of scientific endeavors. This manual is an invaluable source of laboratory protocols for standard and applied research applications in a range of fields such as biotechnology and microbiology